Economic experiments and access to justice, 1997-1999 - Main, Brian G. M. (UK Data Service, 2001)
There are various institutional arrangements used in courts to encourage pre-trial settlement and, hence, reduce the very obvious costs (both emotional and financial) of going through a trial procedure. This project uses the approach of experimental economics to examine the various distinct civil court procedural arrangements that are aimed at improving access to justice through lowering the expected costs of disputants by enhancing their chances of reaching a pre-trial settlement. This is done in a laboratory setting in which participants assume the role of plaintiff or defendant. To focus on the impact of various cost-shifting rules in force in the course of an experiment, it is arranged that participants do not know against whom they are negotiating (by use of a computer network to organise and co-ordinate the rounds of negotiation). Individuals assume the same role throughout each two-hour laboratory session and up to 12 'cases' are simulated in each session with the position in terms of expected damages, probability of winning and expected costs if it ends in trial, all laid out in advance.